High-energy-density self-supporting negative electrode, negative electrode preparation method and sodium ion battery
By using carbon nanofibers and graphene sheets to construct a three-dimensional network structure in the negative electrode of sodium ion battery, the problems of poor conductivity and low energy density in the prior art are solved, and high energy density and excellent battery performance are achieved.
Patent Information
- Application Number
- CN202510099880.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Due to the material and structural limitations of existing sodium ion battery negative electrodes, the activity and poor conductivity are low, which limits the energy density and performance of the battery.
A three-dimensional network structure is constructed using carbon nanofibers and graphene sheets as a substrate for self-supporting current collectors, and a high-energy density negative electrode is formed through electrospinning technology.
The conductivity and active point of the negative electrode are improved, the rate performance and cycling performance of the battery are enhanced, the cost of the battery is reduced, and the energy density is improved.
Smart Images

Figure CN119833562A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a high energy density self-supporting negative electrode, a method for preparing the negative electrode, and a sodium ion battery. Background Art
[0002] At present, the negative electrode of sodium ion batteries is mainly coated on the current collector by the negative electrode slurry, and the mainstream self-supporting current collector of sodium ion batteries is aluminum foil. However, the mass of aluminum foil accounts for a considerable proportion of the entire battery, which has a certain restriction on the energy density of the battery. Moreover, the smooth surface of the aluminum foil has a limited contact area with the negative electrode material and the bonding force at the interface between the two is also small. During the insertion and extraction process of sodium ions, the negative electrode material may fall off the current collector due to the change in volume. In addition, when the negative electrode slurry is coated on the current collector, a binder needs to be added to ensure good contact between the active material and the current collector. However, the binder does not contribute to the capacity in the battery, which further reduces the energy density of the battery. At the same time, the excessive use of electrochemically inert binders increases the internal resistance of the electrode, reduces the utilization rate and kinetic performance of the active material, and further affects the rate performance and cycle performance of the battery. Therefore, the development of high energy density self-supporting sodium ion battery negative electrodes is of great significance to the development of sodium ion batteries. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art that the activity is low and the conductivity is poor due to the limitations of materials and negative electrode structures, and provide a high-energy-density self-supporting negative electrode, a method for preparing the negative electrode and a sodium-ion battery. Carbon nanofibers and graphene sheets are used to construct a three-dimensional network structure on the high-energy-density self-supporting negative electrode, thereby increasing the attachment area of the negative electrode substrate, thereby achieving the purpose of increasing the active sites of the negative electrode and improving the conductivity of the negative electrode. On this basis, a more stable method for preparing a self-supporting negative electrode can be obtained, and a sodium-ion battery with more stable performance can be obtained.
[0004] The purpose of the present invention is mainly achieved through the following technical solutions: A high energy density self-supporting negative electrode, comprising a plurality of self-supporting current collectors, wherein the substrate of the self-supporting current collectors is composed of carbon nanofibers and graphene sheets; In the substrate, the carbon nanofibers account for 80% to 95% by weight, and the graphene sheets account for 5% to 20% by weight; The carbon nanofibers form a three-dimensional network structure through electrostatic spinning; The graphene sheets are interspersed and embedded in the three-dimensional network structure to form a three-dimensional network structure; The self-supporting current collector has a surface area of 5 mg / cm 2 ~8mg / cm 2 The surface density of the negative electrode slurry is coated.
[0005] In the prior art, the negative electrode of a sodium ion battery is usually manufactured using a single material, such as using hard carbon as the main negative electrode material and an aluminum foil current collector or an aluminum-based composite current collector. However, both types of current collectors occupy a relatively high mass, which has a certain impact on the overall energy density of the sodium ion battery, thereby limiting the application environment of the sodium ion battery.
[0006] The high energy density self-supporting negative electrode in the present invention uses carbon nanofibers and graphene sheets to prepare the current collector, and the carbon nanofibers and the graphene sheets can form a three-dimensional network structure. Since graphene is a sheet structure, when the graphene sheets and carbon nanofibers are mixed, the graphene sheets are distributed in the carbon nanofibers, and the substrate formed has better stress strain capacity in bending in different dimensions, thereby showing excellent flexibility; at the same time, the graphene sheets and carbon nanofibers form a three-dimensional network structure, and the three-dimensional network structure formed by the graphene sheets and carbon nanofibers can have better conductivity and more active sites, does not require the use of a binder, and is light in weight, further improving the energy density of the sodium ion battery using the high energy density self-supporting negative electrode of the present invention.
[0007] Regarding the three-dimensional network structure, the carbon nanofibers in the prior art can form a three-dimensional network structure during electrospinning, but the carbon nanofibers in the present invention are mixed with graphene sheets during electrospinning, and the graphene sheets and carbon fibers are electrospun together in a mixed state. Different from the prior art in which graphene is attached to a three-dimensional network structure, the graphene sheets in the present invention can synergistically change with the carbon fibers, and the graphene sheet structure provides higher stability for the stress strain of the fiber in lateral stretching. The carbon nanofiber structure further puts the graphene sheets in a high tensile state, and the resulting constraint force makes the graphene sheets highly continuous, overcoming the discontinuity of the graphene sheets spinning alone. In this process, the graphene sheets are interspersed and embedded in the carbon nanofibers to form a three-dimensional network structure that is more three-dimensional than the three-dimensional network structure.
[0008] On this basis, in the three-dimensional network structure formed by graphene sheets and carbon nanofibers, because the sheet structure of graphene sheets provides more reactive sites in the lateral direction, it can better contact with active substances, thus effectively improving the rate performance. Because of the conductivity of graphene sheets themselves, the base conductivity of the self-supporting current collector formed by graphene sheets and carbon nanofibers is higher.
[0009] In general, the high energy density self-supporting negative electrode of the present invention is formed into a substrate by a combination of carbon nanofibers and graphene sheets. Since the graphene sheets and carbon nanofibers in the substrate can form a three-dimensional network structure, more holes can be provided for the negative electrode substrate to attach. The graphene sheets in the present embodiment exist simultaneously in a variety of sizes within the range of 0.5um~2um. On this basis, the special structure of the graphene sheets can be used by carbon nanofibers and graphene sheets to achieve the purpose of building a more three-dimensional three-dimensional network structure. By controlling the size of the graphene sheets, not only can the continuity of electron transmission be increased in the lateral direction to improve the conductivity of the substrate, but also because graphene is a sheet structure, the graphene sheets are distributed in the carbon nanofibers, and the substrate formed has better stress strain capacity in bending in different dimensions, thereby showing excellent flexibility and improving the self-supporting flexibility of the substrate. Compared with single carbon nanofibers, the addition of graphene sheets has a larger specific surface area, which increases the contact area between the substrate and the negative electrode, and the surface contains a small amount of functional groups, which further enhances the negative electrode connection force through electrostatic adsorption; the sheet can be coated on the surface of the negative electrode particles, strengthening the contact surface between particles and providing an effective way for electron transfer, thereby enhancing the battery rate performance. The carbon fiber substrate obtained by electrospinning by this method has a developed three-dimensional porous structure. The three-dimensional porous structure of the substrate can make the negative electrode well coated on it without using a binder, and the side increases the proportion of active substances in the whole. The binder does not provide capacity, and removing it increases the overall capacity of the active material to play a higher role, thereby improving the energy density of the battery. The three-dimensional porous system is an open and developed three-dimensional system compared to the two-dimensional plane system. When the negative electrode material is coated, it is not just a surface contact. The three-dimensional porous system provides more contact sites for the negative electrode. The negative electrode can be well attached to the substrate without adding a binder during the coating process, increasing the proportion of active materials in the entire battery, further improving the energy density of the battery and reducing the battery cost. At the same time, the cycle performance of the battery without the addition of a binder has also been significantly improved. Most importantly, the weight of the carbon fiber substrate is significantly less than that of aluminum foil, and the three-dimensional porous system can provide more active sites for contact with the active substances, thereby enhancing the rate performance of the battery.
[0010] Furthermore, the diameter of the carbon nanofibers is 100-500 nm; The size of the graphene sheet is 0.5-2 um.
[0011] Furthermore, in the negative electrode slurry, the solid components of the negative electrode slurry include 90% to 97% of negative electrode active material, 0.5% to 5% of conductive agent, and 2.5% to 5% of dispersant by weight.
[0012] The negative electrode active material is hard carbon, the binder is one or more of styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile and polyacrylate, and the dispersant is sodium carboxymethyl cellulose.
[0013] Sodium carboxymethyl cellulose (CMC-Na) is a carboxymethylated derivative of cellulose and is the main ionic cellulose gum. Sodium carboxymethyl cellulose is usually an anionic polymer compound obtained by reacting natural cellulose with caustic soda and monochloroacetic acid, and its molecular weight ranges from several thousand to one million. Since the negative electrode solvent is water, sodium carboxymethyl cellulose is more easily dispersed in water, so the present invention uses sodium carboxymethyl cellulose.
[0014] A method for preparing a high energy density self-supporting negative electrode comprises the following steps: Dissolving an appropriate amount of graphene sheets in a solvent and subjecting the solvent to ultrasonic treatment to obtain a solution in which the graphene sheets are uniformly dispersed; Dissolving a carbon-containing polymer in the solution in which the graphene sheets are uniformly dispersed, stirring and mixing to obtain a mixed solution, obtaining a spinning solution through the mixed solution, and then electrospinning to obtain as-spun carbon nanofibers; The as-spun carbon nanofibers are pretreated and heat-treated to obtain a negative electrode substrate, and a negative electrode slurry is coated on the negative electrode substrate to obtain the high energy density self-supporting negative electrode.
[0015] In the present invention, the negative electrode substrate is a self-supporting current collector. In the process of preparation, the size of the graphene sheet can be controlled by controlling the ultrasonic power and time. The graphene sheet is too large, which is not conducive to electrostatic spinning. The graphene sheet is too small, the lateral contact is too short, and the continuity of electron transmission is weakened. By controlling the size of the graphene sheet, not only can the continuity of electron transmission in the lateral direction be increased to improve the conductivity of the substrate, but also because the graphene is a sheet structure, the graphene sheets are distributed in the carbon nanofibers, and the substrate formed has better stress strain capacity in bending in different dimensions, thereby showing excellent flexibility and improving the self-supporting flexibility of the substrate. Compared with a single carbon nanofiber, the addition of graphene sheets has a larger specific surface area, which increases the contact area between the substrate and the negative electrode, and the surface contains a small amount of functional groups, which further enhances the negative electrode connection force through electrostatic adsorption; the graphene sheet strengthens the contact surface between particles and provides an effective way for electron transmission, thereby enhancing the battery rate performance.
[0016] Different from the traditional carbon substrate with three-dimensional network structure, the substrate of the invention adds graphene sheets of controlled size, so that the substrate with three-dimensional network structure shows higher conductivity and better flexibility. First, graphene sheets are added to the spinning solution. From the electron microscope scanning of the substrate, it can be seen that the graphene sheets are dispersed in the carbon fiber. Due to the excellent mechanical properties and flexibility of graphene itself, the substrate can have better stress strain capacity in bending in different dimensions, thereby showing excellent flexibility. Therefore, the three-dimensional structure composed of graphene sheets and carbon nanofibers is more flexible than a single substrate. Second, due to the unique two-dimensional layered structure of graphene sheets, the three-dimensional network structure composed of graphene sheets and carbon nanofibers is different from the linear structure of single carbon fiber. The sheet structure enhances the lateral conductivity of the substrate and the continuity of electron transmission in the lateral direction. Moreover, compared with a single carbon fiber substrate, the specific surface area is further increased to provide more contact active sites, which can better contact the substrate with the active material, and the conductivity is better and the rate performance is better.
[0017] The carbon nanofibers obtained by electrostatic spinning in the present invention are longer and solid cylindrical. The substrate is a combination of carbon nanofibers and graphene sheets. The substrate material obtained by electrostatic spinning has a more developed and three-dimensional structure, and the graphene sheets can be evenly interspersed and embedded in the carbon fibers. Different from the prior art, the substrate area obtained by suction filtration is less affected by the suction filtration area, which is not conducive to the commercial production of batteries. The substrate area in the present invention is much larger than the substrate area obtained by suction filtration.
[0018] Furthermore, in the solution in which the carbon-containing polymer is dissolved and the graphene sheets are uniformly dispersed, the content of the polyacrylonitrile is 40% to 45%, the content of the graphene sheets is 5% to 10%, and the solvent is N,N-dimethylformamide, based on the total weight of the solution.
[0019] Furthermore, the mixed solution is subjected to ultrasonic dispersion, magnetic stirring, and electrostatic spinning to obtain the spinning solution; Wherein, the frequency of the ultrasonic dispersion is 100-200W, and the time is 1.5-3h; The magnetic stirring speed is 800 rpm to 1200 rpm, and the time is 20 to 24 hours; The following working conditions are adopted during the electrostatic spinning: the positive high voltage is 10-30 kV, the negative high voltage is -2--1 kV; the distance between the spinning outlet and the receiver is 15 cm-25 cm; the propulsion speed is 0.1 mm / min-0.3 mm / min.
[0020] Furthermore, the pretreatment of the as-spun carbon nanofibers comprises the following steps: Keep warm at 200~400℃ for 60~240min; The heat treatment of the as-spun carbon nanofibers comprises the following steps: Maintain a temperature of 500-1000°C in an inert atmosphere for 1-5 hours.
[0021] In the present invention, pre-oxidation and carbonization are the processes of converting the polymer fibers obtained by electrospinning into carbon fibers, the purpose of which is to increase the mechanical strength and thermal stability of the fibers so that they can be used under high temperature and high strength conditions. Pre-oxidation can partially oxidize elements such as hydrogen, oxygen and nitrogen in the polymer fibers to form oxides with a high oxygen content, thereby reducing the amount of gas released during fiber carbonization, reducing the internal stress and thermal shrinkage of the fibers during fiber carbonization, and improving carbonization efficiency. Carbonization is the process of pyrolyzing the pre-oxidized polymer fibers into carbon fibers at high temperatures. By controlling the carbonization temperature and time, the thermal stability, density and crystallinity of the fibers can be controlled, thereby obtaining carbon fibers with desired properties.
[0022] The pre-oxidation can partially oxidize elements such as hydrogen, oxygen and nitrogen in the polymer fiber to form oxides with a high oxygen content, thereby reducing the amount of gas released during fiber carbonization, reducing the internal stress and thermal shrinkage of the fiber during fiber carbonization, and improving carbonization efficiency. If the pre-oxidation is insufficient (the temperature is too low and the time is too short, such as 200°C, 1h), the fiber is prone to defects such as voids during carbonization, and the substrate flexibility deteriorates and the brittleness increases; excessive pre-oxidation (such as too high temperature and too long time 400°C, 2h) affects the rearrangement of the fiber structure. The research results show that as the temperature increases, the tensile properties and moisture content of carbon fibers gradually increase, and the mass loss rate increases rapidly between 220 and 250°C. In addition, the cyclization degree increases particularly quickly between 220 and 250°C, the cyclization reaction mainly occurs at around 220°C, the cyclization reaction is basically complete at 250°C, and a pre-oxidized felt with a better pre-oxidation degree is obtained at 265°C. Only pre-oxidized felt with a good degree of pre-oxidation can maintain the fiber shape after high-temperature carbonization, and obtain carbon nanofibers with a diameter between 100nm and 200nm and good fiber shape. Therefore, it is more appropriate to choose 250~300℃ and 90min~150min.
[0023] The heat treatment is carried out under an inert atmosphere of N2 at a temperature of 500°C to 800°C for 2 to 3 hours, and finally a self-supporting current collector is obtained. At this temperature, the carbonization yield is high, and the skeleton structure is rarely damaged when removing heteroatoms other than carbon.
[0024] Furthermore, after obtaining the negative electrode substrate, the mixed and uniformly dispersed negative electrode slurry is uniformly coated on the self-supporting current collector and dried to set the shape; The dried and shaped self-supporting current collector is rolled and die-cut to obtain the negative electrode sheet.
[0025] A sodium ion battery, comprising a positive electrode, a negative electrode, a separator, an electrolyte and a shell; The positive electrode and the negative electrode are contained in a shell, the separator is located between the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting each other, and the electrolyte is filled in the shell; The negative electrode adopts the high energy density self-supporting negative electrode.
[0026] Furthermore, the shell is one of a square aluminum shell, a square soft package or a cylindrical steel shell.
[0027] In summary, the present invention has the following beneficial effects compared with the prior art: The present invention obtains a self-supporting substrate by electrospinning, which is light in weight and helps to improve the energy density of sodium ion batteries. In addition, adding graphene sheets to the substrate significantly improves the flexible self-supporting performance and conductivity of the substrate, further improving the rate performance of the battery. The carbon fiber substrate obtained by electrospinning has a developed three-dimensional network structure with a large specific surface area, the negative electrode activity can fully contact the substrate, and the high reaction activity is beneficial to the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings: Figure 1 is a scanning electron microscope image of the self-supporting current collector of the present invention; Figure 2 The graph shows the cycle performance of sodium ion batteries prepared with different pole pieces of Example 4, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0029] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0030] Embodiment 1: The method for preparing the self-supporting substrate in this embodiment is as follows: The specific preparation steps of uniformly dispersed graphene are as follows: 50 mg of graphene sheets are added to 10 mL of N,N-dimethylformamide (DMF) and ultrasonically treated at 150 W for 1.5 hours to obtain a uniformly dispersed mixed suspension. Then, 0.95 g of polyacrylonitrile (PAN) is added to the above uniformly dispersed mixed solution. At this time, in the substrate, by weight, the carbon nanofibers account for 95% and the graphene sheets account for 5%.
[0031] The mixed solution is used to obtain a spinning solution, and then electrospinning is performed to obtain as-spun carbon nanofibers; The magnetic stirring speed is 1000 rpm and the time is 24 hours. The electrospinning conditions include: positive high voltage is 15 KV, negative high voltage is -1.5 KV; the distance between the outlet and the receiver is 19 cm; and the propulsion speed is 0.15 mm / min.
[0032] Pre-treating and heat-treating the as-spun carbon nanofibers to obtain a negative electrode substrate; The pretreatment conditions include preferably 250° C. for 1.5 h; The heat treatment conditions include: inert atmosphere N2, temperature of 500°C, time of 2h, and finally obtaining a flexible self-supporting current collector.
[0033] After obtaining the flexible self-supporting current collector, the preparation of the high energy density self-supporting sodium ion battery negative electrode is as follows: The negative electrode slurry was heated to 8 mg / cm 2 The surface density is coated on a flexible self-supporting current collector; The negative electrode substrate coated on the current collector has a solid component of 97% negative electrode active material, 0.5% conductive agent, and 2.5% dispersant by weight. The drying temperature is 60° C. and the baking time is 1 hour.
[0034] The self-supporting current collector is dried and shaped, and the shaped negative electrode is rolled and die-cut to further increase the contact area between the active material and the negative electrode. The rolling pressure is 15Mpa and the rolling speed is 2m / s.
[0035] The sodium ion battery comprises a positive electrode, a negative electrode, a separator, an electrolyte and a shell; The positive electrode and the negative electrode are contained in a shell, the separator is located between the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting each other, and the electrolyte is filled in the shell; The negative electrode is a high energy density self-supporting negative electrode formed by shaping and rolling.
[0036] The shell is a square aluminum shell, a square soft package or a cylindrical steel shell.
[0037] Embodiment 2: The method for preparing the self-supporting substrate in this embodiment is as follows: The specific preparation steps of uniformly dispersed graphene are as follows: 100 mg of graphene sheets are added to 10 mL of N,N-dimethylformamide (DMF) and ultrasonically treated at 200 W for 1.5 hours to obtain a uniformly dispersed mixed suspension. Then, 0.9 g of polyacrylonitrile (PAN) is added to the above uniformly dispersed mixed solution. At this time, in the substrate, by weight, the carbon nanofibers account for 90% and the graphene sheets account for 10%.
[0038] The mixed solution is used to obtain a spinning solution, and then electrospinning is performed to obtain as-spun carbon nanofibers; The magnetic stirring speed is 800 rpm and the time is 24 hours. The electrospinning conditions include: positive high voltage is 15 KV, negative high voltage is -1.5 KV; the distance between the outlet and the receiver is 19 cm; and the propulsion speed is 0.15 mm / min.
[0039] Pre-treating and heat-treating the as-spun carbon nanofibers to obtain a negative electrode substrate; The pretreatment conditions include preferably 250° C. for 1.5 h; The heat treatment conditions include: inert atmosphere N2, temperature of 500°C, time of 2h, and finally obtaining a flexible self-supporting current collector.
[0040] After obtaining the flexible self-supporting current collector, the preparation of the high energy density self-supporting sodium ion battery negative electrode is as follows: The negative electrode slurry was heated to 8 mg / cm 2 The surface density is coated on a flexible self-supporting current collector; The negative electrode substrate coated on the current collector has a solid component of 97% negative electrode active material, 0.5% conductive agent, and 2.5% dispersant in weight percentage. The drying temperature is 60° C. and the baking time is 1 hour.
[0041] The self-supporting current collector is dried and shaped, and the shaped negative electrode is rolled and die-cut to further increase the contact area between the active material and the negative electrode. The rolling pressure is 15Mpa and the rolling speed is 2m / s.
[0042] The sodium ion battery comprises a positive electrode, a negative electrode, a separator, an electrolyte and a shell; The positive electrode and the negative electrode are contained in a shell, the separator is located between the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting each other, and the electrolyte is filled in the shell; The negative electrode is a high energy density self-supporting negative electrode formed by shaping and rolling.
[0043] The shell is a square aluminum shell, a square soft package or a cylindrical steel shell.
[0044] Embodiment 3: The method for preparing the self-supporting substrate in this embodiment is as follows: The specific preparation steps of uniformly dispersed graphene are as follows: 200 mg of graphene sheets are added to 10 mL of N,N-dimethylformamide (DMF) and ultrasonically treated at 120 W for 2.5 hours to obtain a uniformly dispersed mixed suspension. Then, 0.8 g of polyacrylonitrile (PAN) is added to the above uniformly dispersed mixed solution. At this time, in the substrate, by weight, the carbon nanofibers account for 80% and the graphene sheets account for 20%.
[0045] The mixed solution is used to obtain a spinning solution, and then electrospinning is performed to obtain as-spun carbon nanofibers; The magnetic stirring speed is 1100 rpm and the time is 22 hours. The electrospinning conditions include: positive high voltage is 15 KV, negative high voltage is -1.5 KV; the distance between the outlet and the receiver is 19 cm; and the propulsion speed is 0.15 mm / min.
[0046] Pre-treating and heat-treating the as-spun carbon nanofibers to obtain a negative electrode substrate; The pretreatment conditions include preferably 240°C for 90 min; The heat treatment conditions include: inert atmosphere N2, temperature of 500°C, time of 2h, and finally obtaining a flexible self-supporting current collector.
[0047] After obtaining the flexible self-supporting current collector, the preparation of the high energy density self-supporting sodium ion battery negative electrode is as follows: The negative electrode slurry was heated to 8 mg / cm 2 The surface density is coated on a flexible self-supporting current collector; The negative electrode substrate coated on the current collector has a solid component of 96% negative electrode active material, 1.5% conductive agent, and 2.5% dispersant in weight percentage. The drying temperature is 60° C. and the baking time is 1 hour.
[0048] The self-supporting current collector is dried and shaped, and the shaped negative electrode is rolled and die-cut to further increase the contact area between the active material and the negative electrode. The rolling pressure is 15Mpa and the rolling speed is 2m / s.
[0049] The sodium ion battery comprises a positive electrode, a negative electrode, a separator, an electrolyte and a shell; The positive electrode and the negative electrode are contained in a shell, the separator is located between the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting each other, and the electrolyte is filled in the shell; The negative electrode is a high energy density self-supporting negative electrode formed by shaping and rolling.
[0050] The shell is a square aluminum shell, a square soft package or a cylindrical steel shell.
[0051] Embodiment 4: The method for preparing the self-supporting substrate in this embodiment is as follows: The specific preparation steps of uniformly dispersed graphene are as follows: 100 mg of graphene sheets are added to 10 mL of N,N-dimethylformamide (DMF) and ultrasonically treated at 100 W for 3 hours to obtain a uniformly dispersed mixed suspension. Then, 0.9 g of polyacrylonitrile (PAN) is added to the above uniformly dispersed mixed solution. At this time, in the substrate, by weight, the carbon nanofibers account for 90% and the graphene sheets account for 10%.
[0052] The mixed solution is used to obtain a spinning solution, and then electrospinning is performed to obtain as-spun carbon nanofibers; The magnetic stirring speed is 1200 rpm, and the time is 20 hours. The electrospinning conditions include: positive high voltage is 12KV, negative high voltage is -1KV; the distance between the outlet and the receiver is 21cm; and the propulsion speed is 0.27mm / min.
[0053] Pre-treating and heat-treating the as-spun carbon nanofibers to obtain a negative electrode substrate; The pretreatment conditions include preferably 250° C. for 2 h; The heat treatment conditions include: inert atmosphere N2, temperature of 900°C, time of 2h, and finally obtaining a flexible self-supporting current collector.
[0054] After obtaining the flexible self-supporting current collector, the preparation of the high energy density self-supporting sodium ion battery negative electrode is as follows: The negative electrode slurry was heated to 5 mg / cm 2 The surface density is coated on a flexible self-supporting current collector; The negative electrode substrate coated on the current collector has a solid component of 96% negative electrode active material, 0.5% conductive agent, and 3.5% dispersant in weight percentage. The drying temperature is 60° C. and the baking time is 1 hour.
[0055] The self-supporting current collector is dried and shaped, and the shaped negative electrode is rolled and die-cut to further increase the contact area between the active material and the negative electrode. The rolling pressure is 15Mpa and the rolling speed is 2m / s.
[0056] The sodium ion battery comprises a positive electrode, a negative electrode, a separator, an electrolyte and a shell; The positive electrode and the negative electrode are contained in a shell, the separator is located between the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting each other, and the electrolyte is filled in the shell; The negative electrode is a high energy density self-supporting negative electrode formed by shaping and rolling.
[0057] The shell is a square aluminum shell, a square soft package or a cylindrical steel shell.
[0058] Embodiment 5: The method for preparing the self-supporting substrate in this embodiment is as follows: The specific preparation steps of uniformly dispersed graphene are as follows: 100 mg of graphene sheets are added to 10 mL of N,N-dimethylformamide (DMF) and ultrasonically treated at 150 W for 1.5 hours to obtain a uniformly dispersed mixed suspension. Then, 0.9 g of polyacrylonitrile (PAN) is added to the above uniformly dispersed mixed solution. At this time, in the substrate, by weight, the carbon nanofibers account for 90% and the graphene sheets account for 10%.
[0059] The mixed solution is used to obtain a spinning solution, and then electrospinning is performed to obtain as-spun carbon nanofibers; The magnetic stirring speed is 1000 rpm and the time is 24 hours. The electrospinning conditions include: positive high voltage is 20 KV, negative high voltage is -2 KV; the distance between the outlet and the receiver is 16 cm; and the propulsion speed is 0.1 mm / min.
[0060] Pre-treating and heat-treating the as-spun carbon nanofibers to obtain a negative electrode substrate; The pretreatment conditions include preferably 300°C for 2h; The heat treatment conditions include: inert atmosphere N2, temperature of 800°C, time of 2h, and finally obtaining a flexible self-supporting current collector.
[0061] After obtaining the flexible self-supporting current collector, the preparation of the high energy density self-supporting sodium ion battery negative electrode is as follows: The negative electrode slurry was heated to 7 mg / cm 2 The surface density is coated on a flexible self-supporting current collector; The negative electrode substrate coated on the current collector has a solid component of 97% negative electrode active material, 0.5% conductive agent, and 2.5% dispersant in weight percentage. The drying temperature is 60° C. and the baking time is 1 hour.
[0062] The self-supporting current collector is dried and shaped, and the shaped negative electrode is rolled and die-cut to further increase the contact area between the active material and the negative electrode. The rolling pressure is 15Mpa and the rolling speed is 2m / s.
[0063] The sodium ion battery comprises a positive electrode, a negative electrode, a separator, an electrolyte and a shell; The positive electrode and the negative electrode are contained in a shell, the separator is located between the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting each other, and the electrolyte is filled in the shell; The negative electrode is a high energy density self-supporting negative electrode formed by shaping and rolling.
[0064] The shell is a square aluminum shell, a square soft package or a cylindrical steel shell.
[0065] Comparative Example 1: The carbon-containing polymer is polyacrylonitrile dissolved in stirring and mixing without adding graphene sheets to obtain a spinning solution, and then electrospinning is performed, wherein the carbon-containing polymer is polyacrylonitrile, the content of which is 10%, the solvent is N,N-dimethylformamide, the speed of magnetic stirring is 1000rpm, and the time is 24h. The conditions of the electrospinning include: positive high voltage is 15KV, negative high voltage is -1.5KV; the distance between the outlet and the receiver is 19cm; and the propulsion speed is 0.15mm / min.
[0066] The pretreatment conditions include preferably 250° C. and a time of 2 h; the heat treatment conditions include: in an inert atmosphere of N2, a temperature of 800° C. and a time of 2 h, and finally a self-supporting current collector is obtained.
[0067] A method for preparing a negative electrode for a self-supporting sodium ion battery with high energy density; The negative electrode slurry is coated on the current collector.
[0068] The negative electrode slurry coated on the current collector has a solid content of 97% negative electrode active material, 0.5% conductive agent, and 2.5% dispersant by weight. The surface density of the negative electrode slurry on the self-supporting current collector is 8 mg / cm 2 , the drying temperature is 60℃ and the baking time is 1h.
[0069] The shaped negative electrode is rolled to further increase the contact area between the active material and the electrode. The rolling pressure is 15 MPa and the rolling speed is 2 m / s.
[0070] Comparative Example 2: The difference between this comparative example and comparative example 1 is that, in the negative electrode slurry to be applied, the solid components of the negative electrode slurry include 94.5% of negative electrode active material, 0.5% of conductive agent, 2.5% of dispersant, and 2.5% of binder, by weight percentage.
[0071] The negative electrode slurry is directly coated on aluminum foil, dried, rolled, and die-cut to obtain a negative electrode for a sodium ion battery.
[0072] Table 1 Conductivity of negative electrode sheet and energy density of sodium ion battery Serial number Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Pole conductivity (Scm-1) <![CDATA[4.5×10 -2 ]]> <![CDATA[5.8×10 -2 ]]> <![CDATA[6.0×10 -2 ]]> <![CDATA[6.76×10 -2 ]]> <![CDATA[5.2×10 -2 ]]> <![CDATA[3.1×10 -2 ]]> <![CDATA[5.5×10 -2 ]]> Battery energy density (Wh / kg) 118 120 116 125 121 100 115 Table 2 Performance of different battery rates From Table 1, Table 2 and Figure 2It can be seen that compared with a substrate without graphene, adding graphene sheets and controlling the size of the graphene sheets can significantly improve the conductivity of the battery, and the flexibility and self-support of the substrate are also improved. Figure 1 The performance of the self-supporting current collector in the scanning electron microscope can be observed intuitively. Figure 2 By comparison, it can be seen that when the carbon fiber substrate with graphene sheets is used as the current collector, the energy density is increased from 115 Wh / kg to 125Wh / kg, and the battery cycle performance is also significantly improved due to the absence of a binder. At the same time, it can be seen from Table 2 that the appropriate pre-oxidation temperature and time and oxidation temperature and time are beneficial to the conductivity of the substrate.
[0073] This embodiment Figure 1 Graphene in the graphene sheet is a graphene sheet. Figure 1 It can be observed that the graphene sheets are embedded in the carbon nanofibers through electrospinning, and are not independently interspersed on the fibers. Different from the prior art method of attaching graphene to carbon fibers, although a three-dimensional structure can also be constructed, the physical or electrostatic adsorption of graphene sheets and carbon nanofibers is prone to change during use, while the embedded structure in this embodiment firmly combines the graphene sheets and carbon nanofibers, thereby greatly improving the stability of the substrate.
[0074] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high energy density self-supporting negative electrode, comprising a plurality of self-supporting current collectors, characterized in that: The substrate of the self-supporting current collector is composed of carbon nanofibers and graphene sheets; In the substrate, the carbon nanofibers account for 80% to 95% by weight, and the graphene sheets account for 5% to 20% by weight; The carbon nanofibers form a three-dimensional network structure through electrostatic spinning; The graphene sheets are interspersed and embedded in the three-dimensional network structure to form a three-dimensional network structure; The self-supporting current collector has a surface area of 5 mg / cm 2 ~8mg / cm 2 The surface density of the negative electrode slurry is coated.
2. A high energy density self-supporting negative electrode according to claim 1, characterized in that: The diameter of the carbon nanofiber is 100nm~500nm; The size of the graphene sheet is 0.5um~2um.
3. A high energy density self-supporting negative electrode according to claim 1, characterized in that: In the negative electrode slurry, the solid components of the negative electrode slurry include 90% to 97% of negative electrode active material, 0.5% to 5% of conductive agent, and 2.5% to 5% of dispersant by weight.
4. A method for preparing a high energy density self-supporting negative electrode, characterized in that: The following steps are involved: Dissolving graphene sheets in a solvent and subjecting the solvent to ultrasonic treatment to obtain a solution in which the graphene sheets are uniformly dispersed; Dissolving the carbon-containing polymer in the graphene sheet solution and stirring and mixing to obtain a mixed solution having a graphene sheet content of 5% to 10% and a carbon-containing polymer content of 40-45%, based on the total weight of the mixed solution; The mixed solution is used to obtain a spinning solution, and then electrospinning is performed to obtain as-spun carbon nanofibers; The as-spun carbon nanofibers are pre-treated and heat-treated to obtain a negative electrode substrate having a three-dimensional network structure. The negative electrode slurry is prepared at a concentration of 5 mg / cm 2 ~8mg / cm 2 The high energy density self-supporting negative electrode as claimed in any one of claims 1 to 3 is obtained by coating the negative electrode substrate with a surface density of 1.50%.
5. The method for preparing a high energy density self-supporting negative electrode according to claim 4, characterized in that: The carbon-containing polymer is dissolved in the solution in which the graphene sheets are uniformly dispersed, and the total weight of the mixed solution is calculated. The carbon-containing polymer is polyacrylonitrile, the content of the polyacrylonitrile is 40% to 45%, the content of the graphene sheets is 5% to 10%, and the solvent is N,N-dimethylformamide.
6. The method for preparing a high energy density self-supporting negative electrode according to claim 4, characterized in that: The mixed solution is subjected to ultrasonic dispersion, magnetic stirring and electrostatic spinning to obtain the spinning solution; Wherein, the frequency of the ultrasonic dispersion is 100W~200W, and the time is 1.5h~3h; The magnetic stirring speed is 800 rpm to 1200 rpm, and the time is 20 h to 24 h; The following working conditions are adopted during the electrostatic spinning: the positive high voltage is 10kV~30kV, the negative high voltage is -2kV~-1kV; the distance between the spinning outlet and the receiver is 15cm~25cm; the propulsion speed is 0.1mm / min~0.3mm / min.
7. The method for preparing a high energy density self-supporting negative electrode according to claim 4, characterized in that: The pretreatment of the as-spun carbon nanofibers comprises the following steps: Keep warm at 200℃~400℃ for 60min~240min; The heat treatment of the as-spun carbon nanofibers comprises the following steps: Maintain the temperature of 500℃~1000℃ in an inert atmosphere for 1h~5h.
8. The method for preparing a high energy density self-supporting negative electrode according to claim 4, characterized in that: After obtaining the negative electrode substrate, the mixed and uniformly dispersed negative electrode slurry is uniformly coated on the self-supporting current collector and dried to set the shape; The dried and shaped self-supporting current collector is rolled and die-cut to obtain the negative electrode sheet.
9. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode, a negative electrode, a separator, an electrolyte and a shell; The positive electrode and the negative electrode are contained in a shell, the separator is located between the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting each other, and the electrolyte is filled in the shell; The negative electrode adopts a high energy density self-supporting negative electrode as described in any one of claims 1 to 3.
10. A sodium ion battery according to claim 9, characterized in that: The shell is a square aluminum shell, a square soft package or a cylindrical steel shell.
Citation Information
Patent Citations
Method for preparing flexible MoS2 / CNFs sodium ion battery negative electrode material by combining electrostatic spinning and hydrothermal method, and product
CN108878808A
Flexible battery pole piece and battery
CN114792779A
Carbon nanofiber composite material, self-supporting electrode, battery, preparation method and application
CN117988098A
Fibrous current collector comprising carbon NANO fiber, electrode using the same, and method of manufacturing the same
KR1020110125811A
Three-dimensional porous-structured current colletor, method of manufacturing the same, electrode including the same, method of manufacturing the same electrode, and electrochemical device including the same current colletor
KR1020160062617A
Cited By
Composite pole piece, preparation method and sodium ion battery
CN120809730A